ETHNOCULTURAL AND CONFESSIONAL DIVERSITY AS FACTORS OF CONSOLIDATION OF RUSSIAN SOCIETY - Sergey Alekseyevich Vorontsov; Aleksandr Vasilyevich Ponedelkov; Rafik Khammatovich Usmanov (Современная наука и инновации)
The article explores possible directions for strengthening the unity of the Russian civic nation with the actualization of competition between ethnic and civic identities; the assessments of experts of a number of Russian subjects concerning polyethnicity and polyconfessionality, the effectiveness of the implementation of the national policy and the interaction of state authorities and local self-government with national and cultural entities are analyzed.